Strategy to utilize amorphous phase of semiconductor toward excellent and reliable photochemical water splitting performance: Roles of interface dipole moment and reaction parallelization. (28th September 2021) - Choi, Heechae; Han, HyukSu; Moon, Seong‐I; Je, Minyeong; Lee, Seungwoo; Kwon, Jiseok; Kim, Seungchul; Lee, Kwang‐Ryeol; Ali, Ghulam; Mathur, Sanjay; Paik, Ungyu; Qiao, Shi‐Zhang; et al.
Summary: The roles of amorphous phases in photochemical water splitting of semiconductors are still in debate, as the effects of the amorphous phase are largely irregular even in a single material. We presumed that the photochemistry of crystal‐amorphous mixed semiconductor systems would be governed by the interface characteristics, and conducted a systematic study to understand the origins of the largely varying photochemical reaction of semiconductors having an amorphous phase. First‐principles calculations on crystalline anatase and amorphous TiO2 showed that the coexistence of crystalline and amorphous TiO2 and the exposure of the phase boundary are advantageous due to the accelerated charge separation by interface dipole moment and the parallelizable oxygen evolution reaction at the boundary. Our computation‐based strategies were demonstrated in our experiments: only the TiO2 nanoparticle and nanotube having partial amorphization on surfaces have highly enhanced photocatalytic water splitting performances (approximately 700%) compared to the pristine and completely amorphized TiO2 systems. Abstract : Photocatalytic water splitting activities of c‐a junctioned TiO2 are largely affected by interface electric fields phase boundary exposed to the surface. This work successfully demonstrated two new important factors in the design of photoactive semiconductors: interface electric field and surface parallelization.